Experimental stress during molt suggests the evolution of condition‐dependent and condition‐independent ornaments in the king penguin. Issue 2 (20th December 2017) - Schull, Quentin; Robin, Jean‐Patrice; Dobson, F. Stephen; Saadaoui, Hédi; Viblanc, Vincent A.; Bize, Pierre
Abstract: Sexual selection and social selection are two important theories proposed for explaining the evolution of colorful ornamental traits in animals. Understanding signal honesty requires studying how environmental and physiological factors during development influence the showy nature of sexual and social ornaments. We experimentally manipulated physiological stress and immunity status during the molt in adult king penguins ( Aptenodytes patagonicus ), and studied the consequences of our treatments on colourful ornaments (yellow‐orange and UV beak spots and yellow‐orange auricular feather patches) known to be used in sexual and social contexts in this species. Whereas some ornamental features showed strong condition‐dependence (yellow auricular feather chroma, yellow and UV chroma of the beak), others were condition‐independent and remained highly correlated before and after the molt (auricular patch size and beak UV hue). Our study provides a rare examination of the links between ornament determinism and selection processes in the wild. We highlight the coexistence of ornaments costly to produce that may be honest signals used in mate choice, and ornaments for which honesty may be enforced by social mediation or rely on genetic constraints. Abstract : How environmental and physiological factors during development influence the showy nature of sexual and social ornaments remains overlooked.We experimentally manipulated physiological stress and immunity status during the moult in adult king penguins ( Aptenodytes patagonicus ). Our study provides evidence for the evolution of condition‐dependent and condition‐independent ornaments in the king penguin, and suggests that variation in the cost of ornament production could be rooted in their main use for mate attraction or for signalling social status. Our study provides a rare examination of the links between ornament determinism and selection processes in the wild.